Tensor product for g-fusion frame in hilbert C^*-modules - Nhari, fakhr-dine; Rossafi, Mohamed; Aribou, Youssef (Jurnal Matematika, Statistika dan Komputasi, 2023)
In this paper, we stady the tensor product of g-fusion frame in Hilbert C^*-modules and we give the frame operator for a pair of g-fusion bessel sequences in tensor product of Hilbert C^*-modules.